Linked Open Data - Creating Knowledge Out of Interlinked Data Results of the LOD2 Project - Auer, Sören; Bryl, Volha; Tramp, Sebastian (Lecture Notes in Computer Science, 2014)
Database Management; Artificial Intelligence (incl. Robotics); Information Systems and Communication Service